YUNNAN PEOPLE IN BAN HUAI PHUENG VILLAGE DOI MAE SALONG, MAE FAH LUANG DISTRICT, CHIANG RAI PROVINCE - Daungkam, Issareeya; Trarungruang, Napakkanya (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
The study is quality research, aiming to study the dynamic history of Yunnan people in Chiang Rai. The methods include documentation, in-depth interviewing by picking villages, interview primary sources that have prominent roles in their villages such as leaders, co-founders, professors and citizens living in Ban Huai Phueng Village. Other research methods include data collection, questionnaires and descriptive research. The research revealed that Chiang Rai Province and Yunnan Province in China are located in close proximity due to their mountainous terrains and rivers that have been shared by the ethnic groups since the ancient period. These groups built economic and cultural connections which are close to Yunnan province for a long time. The northern parts of Thailand also have cultural backgrounds similar to Yunnan’s. Chiang Rai is the place that Yunnan people along with The Kuomintang, often referred to in English as the Nationalist Party of China immigrated to. Even though these Yunnan people were affected by worldwide trends, they closely upheld their traditional ways of living which were integrated by Sino-Thais and the conventional Chinese. This was reflected in the multi-language usage like Thai, Chinese, Northern Thai, and local ones. They lived altogether like the establishment, Mei Si Luo, which means peace in Chinese